Understanding how outcomes are measured in workplace physical activity interventions: a scoping review - Stacey Johnson; Jean-Philippe Regnaux; Adrien Marck; Geoffroy Berthelot; Joana Ungureanu; Jean-François Toussaint (BMC, 2018)
Abstract Background An inverse relationship exists between physical activity and many non-communicable diseases, such as obesity. Given the daily time spent, a logical domain to reach an adult population for intervention is within and around the workplace. Many government bodies, including the World Health Organization (WHO), include worksite health promotions (WHPs) targeted at increasing physical activity as a public health intervention. The aim of this scoping review was to determine what was measured (outcomes) and how they were measured (evaluation tools) during workplace physical activity interventions in order to identify gaps and implications for policies and practice. Methods A scoping review was executed in April 2017 via PubMed, SPORTDiscus, EBSCOhost and the Cochrane Library. This search included articles published between January 2008 to February 2017 in order to coincide with the WHO's Global Plan of Action on Worker's Health. Extracted information was arranged into data collection grids. Cross-analysis of measured outcomes with their corresponding evaluation tools was completed. A quality assessment based on study design was executed. Results Identification of 732 records was made and ultimately 20 studies and reviews that met criteria were selected. Researchers themed 9 primary measured outcomes. Studies utilized various forms of both objective and subjective evaluation methods. Three primary evaluation methods were categorized: biologic, electronic and declarative tools. The researchers discovered 92 unique tools: 27 objective and 65 subjective, within these parameters. Conclusion Study quality, measurement tools and data collection were heterogeneous making analysis of effect comparisons problematic and unreliable. Much of the published research does not employ robust statistical analysis making effects difficult to ascertain. Considering the variety of both measured outcomes and evaluation tools, only educated inferences can be made as to the effectiveness and efficiency of WHPs. More standardized measurement practices are therefore suggested for assessment efficiency.